(untitled) (Economics and region, 2016)
The current policy of region food sphere state regulation was investigated. The main objectives of state regulation of branches and spheres of food security in the region and a number of ways to implement them were outlined. The necessity of introduction of marketing tools in the system of region food sphere state regulation was justified. Areas of marketing impact of government regulation on the food supply system were specified.